BAUS consensus document for the management of male genital emergencies: priapism. (10th April 2018) - ; Muneer, Asif; Brown, Gareth; Dorkin, Trevor; Lucky, Marc; Pearcy, Richard; Shabbir, Majid; Shukla, Chitranjan J.; Rees, Rowland W.; Summerton, Duncan J.
Abstract : Male genital emergencies relating to the penis and scrotum are rare and require prompt investigation and surgical intervention. Clinicians are often unfamiliar with the management of these conditions and may not work in a specialist centre with on‐site expertise in genitourethral surgery. A series of consensus statements have been developed by an expert consensus committee comprising members of the BAUS Section of Andrology and Genitourethral Surgery together with experts from urology units throughout the UK. Priapism requires prompt assessment and treatment and these consensus statements provide guidance for UK practice.